ZTA ceramic material as well as preparation method and application thereof

By introducing spinel into ZTA ceramic materials and using its nailing effect to refine the ceramic grains, the problem of degradation of existing ZTA ceramic materials is solved, and the combination of high strength, toughness and hardness is achieved, and safety is avoided. Hidden danger.

CN119430882APending Publication Date: 2025-02-14CHAOZHOU THREE CIRCLE GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411598772.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

Smart Images

  • Figure BDA0005127683350000081
    Figure BDA0005127683350000081
  • Figure BDA0005127683350000091
    Figure BDA0005127683350000091
  • Figure BDA0005127683350000092
    Figure BDA0005127683350000092
Patent Text Reader

Abstract

The invention discloses a ZTA ceramic material as well as a preparation method and application thereof. The ZTA ceramic material comprises a ceramic matrix and an additive, the additive comprises spinel; the molecular formula of the spinel is AB2O4, A is selected from at least two of Zn, Mg and Ca, and B is Al. According to the ZTA ceramic material disclosed by the invention, the spinel is added, so that the ZTA ceramic material has relatively high toughness, strength and hardness, the hardness is greater than 16.5 GPa, and the bending strength is not less than 600MPa. In addition, the ZTA ceramic material provided by the invention also has a relatively small grain size, and the average grain size is less than 1 [mu] m. The ZTA ceramic material disclosed by the invention is prepared into a ceramic sintered body which can be applied to products such as joint prostheses such as hip joint prostheses and ceramic choppers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a ZTA ceramic material and a preparation method and application thereof. Background Art

[0002] Zirconia toughened alumina (ZTA) ceramic material is a composite of alumina and zirconia in a certain proportion, and then the strength and hardness of ZTA ceramics can be improved by refining the particle size of the sintered body. In order to further improve the properties of ZTA ceramic materials, a small amount of additives are usually added to the ZTA ceramic materials, such as Mo, W, a mixture of Mo and W, SrO, Y2O3, etc., so as to form slender anisotropic particles in the ZTA ceramic materials, which have high toughness and high strength characteristics; or from Ca3Ti8Al 12 O 37 、SrTi3Al8O 19 、Ba3TiAl 10 O 20 At least one of the composite oxides is selected and introduced into the ZTA ceramic material, so that columnar crystals with an aspect ratio greater than 3 are formed in the composite ceramic. Although the above ZTA ceramic material has improved strength and toughness by introducing metal phases, columnar crystals, etc., it also has the following problems: (1) When a metal phase is introduced into a ZTA ceramic material, on the one hand, due to the weak metal bond force, ions are easily separated and enter the body environment to trigger various reactions, which poses certain safety hazards; on the other hand, the hardness of the metal phase is relatively low compared to the ceramic phase, thereby reducing the hardness of the ceramic material. (2) When columnar crystals with relatively low hardness are introduced into a ZTA ceramic material, there is also the problem of reduced hardness. Summary of the invention

[0003] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a ZTA ceramic material.

[0004] A second object of the present invention is to provide a method for preparing a ZTA ceramic material.

[0005] A third object of the present invention is to provide a ceramic product.

[0006] A fourth object of the present invention is to provide an application of a ZTA ceramic material in the preparation of medical materials or electronic products.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a ZTA ceramic material, comprising a ceramic matrix and an additive; the additive comprises spinel; the molecular formula of the spinel is AB2O4, wherein A is selected from at least two of Zn, Mg, and Ca, and B is Al

[0009] The present invention introduces spinel into the ceramic matrix. The fine spinel phase itself has high hardness. After sintering, the spinel phase is distributed around the grains of the ceramic matrix. The spinel phase can refine the grains and improve the hardness through the pinning effect. Therefore, the ZTA ceramic material containing the spinel additive has higher hardness while maintaining higher strength and toughness. The ZTA ceramic material is prepared into a ceramic sintered body, which can be applied to joint prostheses such as hip joint prostheses, ceramic splitters and other products.

[0010] The physical properties of the spinel in the present invention are close to those of the ceramic matrix, and the two have good compatibility. In addition, the Zn, Mg, and Ca elements in the spinel are not easy to change valence, and have high stability and high hardness.

[0011] Preferably, the particle size of the spinel is 20-50 nm, for example, it can be selected from 20 nm, 30 nm, 40 nm, and 50 nm. When the particle size of the spinel is in the range of 20 to 50 nm, the spinel is evenly dispersed in the ceramic matrix, and the ceramic sintered body has a higher hardness and sintering density. If the particle size of the spinel is too small, it is difficult to disperse evenly in the ceramic matrix; if the particle size of the spinel is too large, the hardness and sintering density of the ceramic sintered body to which the spinel is added will deteriorate.

[0012] Preferably, the mass ratio of the ceramic matrix to the spinel is (18.4-199):1, for example, it can be selected from 18.4:1, 19:1, 20:1, 21:1, 22:1, 23:1, 25:1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, 36:1, 37:1, 38:1, 39:1, 40:1, 41:1, 42:1, 43:1, 44:1, 45:1, 46:1, 47:1 7:1, 48:1, 49:1, 50:1, 51:1, 52:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1, 190:1, 199:1; further preferably, the mass ratio of the ceramic matrix to the spinel is (20-154):1; more preferably, the mass ratio of the ceramic matrix to the spinel is (30-50):1. If the mass ratio of the ceramic matrix to the spinel is too high, the effect of the spinel is small and the effect of improving the hardness is weak. If the mass ratio of the ceramic matrix to the spinel is too low, the spinel is easily enriched to form large grains, and the hardness and sintering density are deteriorated.

[0013] Preferably, the additive further includes at least one of strontium aluminate and chromium oxide.

[0014] Preferably, the additive further comprises strontium aluminate and chromium oxide.

[0015] Preferably, based on the total mass percentage of the ZTA ceramic material as 100%, the mass percentage of the strontium aluminate is 0.5-3%. For example, the mass percentage of strontium aluminate can be selected from 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%; further preferably, based on the total mass percentage of the ZTA ceramic material as 100%, the mass percentage of strontium aluminate is 1-3%; more preferably, based on the total mass percentage of the ZTA ceramic material as 100%, the mass percentage of strontium aluminate is 1-2%. When the content of strontium aluminate is within the range defined in the present invention, the toughness and strength of the ZTA ceramic material can be significantly improved; if the amount of strontium aluminate added is too high, the hardness will be affected, and the hardness of the ZTA ceramic material will be reduced. If the amount of strontium aluminate added is too low, the toughness and strength of the obtained ZTA ceramic material are insufficient.

[0016] Preferably, based on the total mass percentage of the ZTA ceramic material as 100%, the mass percentage of chromium oxide is 0.1-0.5%, for example, it can be selected from 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, .3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%; further preferably, based on the total mass percentage of the ZTA ceramic material as 100%, the mass percentage of the chromium oxide is 0.2-0.4%. In the present invention, chromium oxide is dissolved in the alumina lattice, causing a certain degree of distortion of the lattice and promoting sintering. If the amount of chromium oxide added is too low, the sintering effect is weak. If the amount of chromium oxide added is too high, it is difficult to completely dissolve, which will hinder sintering.

[0017] Preferably, the ceramic matrix is ​​a ZTA ceramic matrix, that is, a zirconia-toughened alumina ceramic. In the ZTA ceramic matrix, the mass ratio of zirconia to alumina is 1:(3-4), for example, it can be selected from 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 4:1.

[0018] Preferably, the spinel is (Zn 1-x-y Mg x Ca y)Al2O4, wherein 0≤x<0.3, 0≤y<0.3, and x and y are not 0 at the same time; for example, the value of x in spinel can be selected from 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.295, 0.296, 0.297, 0.298 .298, 0.299; the value of y in the spinel can be selected from 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.295, 0.296, 0.297, 0.298, 0.299; further preferably, the spinel is (Zn 1-x- y Mg x Ca y )Al2O4, wherein 0.05≤x<0.3, 0.05≤y<0.3. If the value of x and / or y is greater than 0.3, the temperature in the spinel synthesis process needs to be increased accordingly, and the spinel grains formed exceed 50nm, which is not conducive to improving the hardness of the ZTA ceramic material. When the values ​​of x and y are within the scope of the present invention, on the one hand, the synthesis temperature of the spinel is relatively low, which is conducive to reducing the production cost. On the other hand, the grain size of the spinel formed can be controlled within the range of 20-50nm, and the grain distribution is relatively uniform, which is conducive to improving the hardness of the ZTA ceramic material, so that the hardness of the ZTA ceramic material is greater than 16.5GPa.

[0019] Preferably, the spinel comprises (Zn 0.8 Mg 0.1 Ca 0.1 )Al2O4、(Zn 0.85 Ca 0.15 )Al2O4、(Zn 0.8 Mg 0.2 )Al2O4、(Zn 0.62 Mg 0.28 Ca 0.1 )Al2O4、(Zn 0.89 Mg 0.01 Ca 0.1 )Al2O4、(Zn 0.89 Mg0.1 Ca 0.01 )Al2O4、(Zn 0.62 Mg 0.1 Ca 0.28 )Al2O4.

[0020] Preferably, the spinel is prepared by mixing at least two selected from magnesium alkoxide, zinc alkoxide and calcium salt with aluminum alkoxide, followed by hydrolysis reaction, aging and calcining.

[0021] Preferably, the aging time is 1 to 3 hours, for example, the aging time can be selected from 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours.

[0022] Preferably, the temperature of the hydrolysis reaction is 55-75°C, for example, can be selected from 55°C, 57°C, 59°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 75°C.

[0023] Preferably, the aluminum alkoxide includes at least one of aluminum isopropoxide, aluminum ethoxide, aluminum methoxide, and aluminum sec-butoxide.

[0024] Preferably, the magnesium alkoxide includes at least one of magnesium isopropoxide, magnesium ethoxide, magnesium methoxide and magnesium butoxide.

[0025] Preferably, the zinc alkoxide includes at least one of zinc isopropoxide, zinc ethoxide, zinc methoxide and zinc butoxide.

[0026] Preferably, the calcium salt includes at least one of calcium chloride, calcium nitrate and calcium bicarbonate.

[0027] Preferably, the calcination temperature is 650°C to 950°C, for example, can be selected from 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C.

[0028] Preferably, the calcination time is 2 h to 10 h, for example, can be selected from 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, and 10 h.

[0029] When the calcination temperature is 650℃~950℃ and the calcination time is 2~10h, it is most conducive to the transformation into the spinel phase, and the prepared spinel has smaller grains. The spinel with smaller particle size is conducive to improving the hardness and sintering density of ZTA ceramic materials. If the temperature is lower than 650℃, or the calcination time is lower than 2h, it is difficult for the raw material to be transformed into the spinel phase; if the calcination temperature exceeds 950℃, or the calcination time is higher than 10h, the prepared spinel grains will become larger, and the required spinel grains with a particle size range of 20-50nm cannot be obtained, which will lead to the deterioration of the hardness and sintering density of the ceramic sintered body added with the spinel.

[0030] Preferably, the preparation method of the spinel is: at least two selected from magnesium alkoxide, zinc alkoxide, and calcium salt are mixed with aluminum alkoxide and alcohol solution to obtain a mixture; water is added dropwise to the mixture and mixed and reacted at 55-75°C, aged for 1-3 hours after the mixed reaction, heated to 100-120°C to recover the alcohol solution to obtain a solid product, and then the solid product is calcined at 650-950°C for 2-10 hours to obtain the spinel.

[0031] The present invention first prepares spinel and then adds the spinel as a raw material into the raw material for preparing the ZTA ceramic material. After sintering, the ZTA ceramic material forms a spinel structure with relatively high hardness. If it is added in the form of oxides, for example: (Zn 1-x-y Mg x Ca y )Al2O4 as an example, zinc oxide, magnesium oxide, calcium oxide and aluminum oxide are added to the raw materials for preparing ZTA ceramic materials to replace (Zn 1-x-y Mg x Ca y )Al2O4, although ZTA ceramic materials also contain metals such as Zn, Mg, and Ca, the oxides of these elements will partially dissolve into the zirconia lattice in the ZTA ceramic materials, unable to form a spinel phase, and have no contribution to improving the hardness.

[0032] The second aspect of the present invention provides a method for preparing the ZTA ceramic material provided in the first aspect of the present invention, comprising the following steps:

[0033] S1: mixing various raw materials for preparing ZTA ceramic materials, pressing and forming, and obtaining a green body;

[0034] S2: Debinding the green body and then calcining it, and then hot isostatic pressing it and then annealing it to obtain the ZTA ceramic material.

[0035] Preferably, the debinding temperature is 300-400°C, for example, can be selected from 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C.

[0036] Preferably, the debinding time is 3 to 7 hours, for example, can be selected from 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours.

[0037] Preferably, the pressing step is performed using an isostatic water pressure of 180 to 220 MPa.

[0038] Preferably, the calcination temperature in step S2 is 1400-1600°C. For example, the calcination temperature can be selected from 1400°C, 1420°C, 1440°C, 1460°C, 1480°C, 1500°C, 1520°C, 1540°C, 1560°C, 1580°C, and 1600°C.

[0039] Preferably, the calcination time in step S2 is 3 to 7 hours, for example, can be selected from 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours.

[0040] Preferably, the temperature of the hot isostatic pressing treatment is 1350-1500°C, for example, can be selected from 1350°C, 1370°C, 1390°C, 1400°C, 1420°C, 1440°C, 1460°C, 1480°C, 1500°C.

[0041] Preferably, the hot isostatic pressing treatment time is 3 to 7 hours, for example, can be selected from 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours.

[0042] Preferably, the hot isostatic pressing step is performed under inert gas protection.

[0043] Preferably, the inert gas is selected from nitrogen, argon or a combination thereof.

[0044] Preferably, the pressure of the hot isostatic pressing treatment is 120-140 MPa, for example, can be selected from 120 MPa, 122 MPa, 124 MPa, 126 MPa, 128 MPa, 130 MPa, 132 MPa, 134 MPa, 136 MPa, 138 MPa, 140 MPa.

[0045] Preferably, the annealing temperature is 1200-1300°C, for example, can be selected from 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C.

[0046] Preferably, the annealing time is 1 to 10 hours, for example, can be selected from 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours. The role of annealing is to balance the oxygen vacancies generated in the ZTA ceramic material during the hot isostatic pressing process.

[0047] Preferably, step S1 comprises: grinding and mixing the spinel with part of water and part of dispersant, then grinding and mixing with alumina, zirconium oxide, chromium oxide, strontium aluminate, remaining water and remaining dispersant, then mixing with an organic binder, spray drying, and pressing to form. Further preferably, step S1 comprises: ball milling and mixing the spinel with part of water and part of dispersant, then ball milling and mixing with alumina, zirconium oxide, chromium oxide, strontium aluminate, remaining water and remaining dispersant, then mixing with an organic binder, spray drying, and pressing to form.

[0048] Preferably, the organic binder is selected from at least one of polyacrylic acid, hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, triethanolamine, polyethylene glycol (PEG), and polyacrylic acid amine. During the debinding process, the organic binder will be decomposed and discharged.

[0049] Preferably, the mass ratio of the spinel to part of the water is 1:(0.8-1.2), for example, it can be selected from 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2.

[0050] Preferably, the mass ratio of the spinel to part of the dispersant is 100:(0.4-0.6), for example, can be selected from 100:0.4, 100:0.5, 100:0.6.

[0051] Preferably, the dispersant is selected from at least one of polyethylene glycol (PEG) and polyacrylamide.

[0052] The third aspect of the present invention provides a ceramic product, which is made of raw materials including the ZTA ceramic material provided by the first aspect of the present invention; the ceramic product is selected from a joint prosthesis, a sliding bearing or a ceramic splitter.

[0053] The fourth aspect of the present invention provides the use of the ZTA ceramic material provided by the first aspect of the present invention in the preparation of medical materials or electronic products.

[0054] The beneficial effects of the present invention are as follows: the ZTA ceramic material of the present invention can have high toughness, strength and hardness by adding spinel, wherein the hardness is greater than 16.5 GPa and the bending strength is not less than 600 MPa. In addition, the ZTA ceramic material of the present invention also has a smaller grain size, and the average grain size is less than 1 μm. The ZTA ceramic material of the present invention is prepared into a ceramic sintered body, which can be applied to joint prostheses such as hip joint prostheses, ceramic splitters and other products. DETAILED DESCRIPTION

[0055] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0056] The ZTA ceramic matrix refers to a zirconium oxide toughened alumina (ZTA) ceramic material. The present invention introduces an additive containing a spinel phase into the ZTA ceramic matrix, so that the ZTA ceramic material containing the spinel additive has a higher hardness while maintaining the original high strength and toughness of the ZTA ceramic matrix. Therefore, the present invention can introduce an additive containing a spinel phase into the ZTA ceramic matrix in any proportion, and can significantly improve the hardness of the ZTA ceramic material on the basis of the original ZTA ceramic matrix. It is not limited to the ceramic matrix of zirconium oxide and alumina with a specific mass ratio recorded in the embodiments of the present invention. The inventors also tried the ZTA ceramic matrix and other ceramic matrices during the research and development process, and found that the introduction of the spinel additive can significantly improve the hardness of the ZTA ceramic material containing the spinel additive. For the sake of convenience, a specific number of embodiments are selected below to illustrate that the introduction of the spinel additive can enhance the hardness of the ZTA ceramic material.

[0057] The dispersants used in Examples 1 to 15 and Comparative Examples 1 to 10 are all polyethylene glycol (PEG).

[0058] Embodiment 1:

[0059] This example provides a ZTA ceramic material, which is composed of the following components in mass percentage: 74.8% aluminum oxide, 20.9% zirconium oxide, 0.3% chromium oxide, 1.5% strontium aluminate, and 2.5% spinel; the molecular formula of spinel is: (Zn 0.8 Mg 0.1 Ca 0.1 )Al2O4. The particle size of the spinel is 30nm.

[0060] The ZTA ceramic material in this example is prepared by the following preparation method, the specific steps are:

[0061] S1. Aluminum isopropoxide, magnesium isopropoxide, zinc isopropoxide, calcium chloride and isopropanol are mixed and stirred at a molar ratio of 2:0.8:0.1:0.1:97 for 1 hour to obtain an alkoxide mixture, and then deionized water is slowly dripped into the above alkoxide mixture under 65° C. oil bath conditions to react. After the reaction, the mixture is aged for 2 hours, and the oil bath temperature is increased to 105° C. for drying to obtain a gel powder.

[0062] S2, calcining the gel powder obtained in step S1 at low temperature to obtain the desired spinel, namely (Zn 0.8 Mg 0.1 Ca 0.1 )Al2O4; the calcination temperature is 800℃ and the calcination time is 5h.

[0063] S3, the spinel (Zn 0.8 Mg 0.1 Ca 0.1 )Al2O4 is added to deionized water, the weight ratio of spinel to deionized water is 1:1, and then a dispersant is added to make the mass percentage of the dispersant 0.5%, and the mixture is put into a ball mill for 4 hours to obtain the pre-dispersed spinel; then alumina, zirconium oxide, chromium oxide, strontium aluminate, the pre-dispersed spinel, water and the dispersant are added to the ball mill, and alumina balls are used for grinding and mixing to obtain a mixed slurry, in which the solid content of the mixed slurry is 50% and the mass percentage of the dispersant is 0.5%;

[0064] S4, adding 2% by weight of an organic binder polyacrylic acid (based on the total weight percentage of aluminum oxide, zirconium oxide, and chromium oxide being 100%), and spray drying to obtain a granular material with fluidity;

[0065] S5, pressing and then isostatically pressing at 200 MPa to make a sheet-like body;

[0066] S6. Place the green body in a degreasing furnace, slowly heat it to 350°C and keep it for 5 hours to decompose and discharge the organic binder;

[0067] S7, pre-sintering the green body from which the organic binder is removed at 1500° C. for 5 h in an air atmosphere, and then sintering at 1400° C. for 5 h under hot isostatic pressing at 130 MPa in an inert gas to obtain a dense sintered body;

[0068] S8. Annealing the sintered body at 1300° C. for 2 h in an air atmosphere to balance the oxygen vacancies generated during the hot isostatic pressing sintering process, thereby obtaining the ZTA ceramic material in this example.

[0069] The ZTA ceramic material in this example is cut, ground and polished to obtain a test sample for performance testing.

[0070] Example 2

[0071] The only difference between this example and Example 1 is that the calcination temperature of step S2 in the preparation method of this example is 650°C.

[0072] Example 3

[0073] The only difference between this example and Example 1 is that the calcination temperature of step S2 in the preparation method of this example is 950°C.

[0074] Example 4

[0075] The only difference between this example and Example 1 is that the calcination time of step S2 in the preparation method of this example is 2 hours.

[0076] Example 5

[0077] The only difference between this example and Example 1 is that the calcination time of step S2 in the preparation method of this example is 10 hours.

[0078] Example 6

[0079] The only difference between this example and Example 1 is that the mass percentage of spinel in this example is 0.5%.

[0080] Example 7

[0081] The only difference between this example and Example 1 is that the mass percentage of spinel in this example is 5.0%.

[0082] Example 8

[0083] The only difference between this example and Example 1 is that the mass percentage of strontium aluminate in this example is 0.5%.

[0084] Example 9

[0085] The only difference between this example and Example 1 is that the mass percentage of strontium aluminate in this example is 3%.

[0086] Embodiment 10 to Embodiment 15

[0087] The only difference between Examples 10 to 15 and Example 1 is that different types of spinels are used.

[0088] Comparative Example 1

[0089] The only difference between this example and Example 1 is that the calcination temperature of step S2 in the preparation method of this example is 600°C.

[0090] Comparative Example 2

[0091] The only difference between this example and Example 1 is that the calcination temperature of step S2 in the preparation method of this example is 1000°C.

[0092] Comparative Example 3

[0093] The only difference between this example and Example 1 is that the calcination time of step S2 in the preparation method of this example is 0.5 h.

[0094] Comparative Example 4

[0095] The only difference between this example and Example 1 is that the calcination time of step S2 in the preparation method of this example is 15 hours.

[0096] Comparative Example 5

[0097] The only difference between this example and Example 1 is that the mass percentage of spinel in this example is 0.2%.

[0098] Comparative Example 6

[0099] The only difference between this example and Example 1 is that the mass percentage of spinel in this example is 8%.

[0100] Comparative Example 7

[0101] The only difference between this example and Example 1 is that strontium aluminate is not added in this example.

[0102] Comparative Example 8

[0103] The only difference between this example and Example 1 is that the mass percentage of strontium aluminate in this example is 5%.

[0104] Comparative Example 9

[0105] The difference between this example and Example 1 is that this example does not include step S1 and step S2; in step S3 of this example, commercially available magnesium aluminum spinel is used for pre-dispersion.

[0106] Comparative Example 10

[0107] The only difference between this example and Example 1 is that the type of spinel used in this example is different.

[0108] The formulations and calcination process parameters of the ZTA ceramic materials in the above-mentioned Examples 1 to 15 and Comparative Examples 1 to 10 are shown in Table 1 below.

[0109] The types of spinels used in the above Examples 1 to 15 and Comparative Examples 1 to 10 are shown in Table 2.

[0110] Table 1 Formula and calcination process parameters of ZTA ceramic materials

[0111]

[0112]

[0113] Table 2 Spinel types

[0114]

[0115]

[0116] Performance Testing

[0117] The hardness, strength and grain size data of the ZTA ceramic materials in Examples 1 to 15 and Comparative Examples 1 to 10 were tested respectively. The specific test methods and compliance requirements are shown in Table 3, and the specific test results are shown in Table 4.

[0118] Table 3 Performance test methods and compliance requirements

[0119]

[0120] Table 4 Test results of hardness, flexural strength and grain size

[0121]

[0122]

[0123] As shown in Table 4, the temperature used in the spinel calcination of Comparative Example 1 is too low, and the calcination time used in Comparative Example 3 is too short. Part of the magnesium oxide is not completely reacted to form a spinel structure, and the obtained spinel particle size is too small. A liquid phase is formed during sintering, and the alumina grains grow, thereby reducing the hardness of the ZTA ceramic materials in Comparative Example 1 and Comparative Example 3. The temperature used in the spinel calcination of Comparative Example 2 is too high, and the calcination time used in Comparative Example 4 is too long. The particle size of the spinel grains is too large, and the effect of inhibiting the growth of alumina grains is weakened, thereby reducing the hardness and strength of the ZTA ceramic materials in Comparative Example 2 and Comparative Example 4. In Comparative Example 5, the amount of spinel added is too small, and the effect of inhibiting the growth of alumina grains is not obvious, so that the size of the alumina grains exceeds 1μm. In Comparative Example 6, the amount of spinel added is too much. Although it can inhibit the growth of alumina grains, the spinel itself is enriched to form large particles, resulting in a decrease in overall hardness. In Comparative Example 7, the amount of strontium aluminate added is small. Although the hardness of the ZTA ceramic material is high, the strength is low. In Comparative Example 8, the amount of strontium aluminate added is large, and the hardness of strontium aluminate itself is low, resulting in low overall hardness of the ZTA ceramic material. Comparative Example 9 uses magnesium aluminum spinel purchased from the market. The spinel particle size is relatively large, and the effect of inhibiting the growth of alumina grains is weak, and the hardness of the obtained ZTA ceramic material is low. The Ca content in the spinel used in Comparative Example 10 is too high, resulting in a decrease in the overall hardness of the ZTA ceramic material.

[0124] Compared with comparative examples 1 to 10, the spinels used in examples 1 to 15 of the present invention are (Zn 1-x-y Mg x Ca y )Al2O4, wherein 0≤x<0.3, 0≤y<0.3, x and y are not 0 at the same time, the hardness of the obtained ZTA ceramic material is greater than 16.5GPa, the bending strength is greater than 600MPa, the average value of the alumina grain size is less than 1.0μm, and it has excellent mechanical properties.

[0125] In summary, in order to solve the problem of low hardness of traditional ZTA materials, the present invention introduces a relatively high hardness AB2O4 spinel phase on the basis of the original ZTA ceramic, wherein A is at least two of Zn, Mg, and Ca, and B is Al; the fine spinel phase itself has high hardness and is distributed around the alumina and zirconia grains after sintering, and the alumina grains are refined through the pinning effect, so that the size of the alumina grains does not exceed 1 μm, thereby improving the hardness of the ZTA material without reducing the strength and toughness. In addition, the present invention does not contain a metal phase and does not have potential safety hazards. After the ZTA ceramic material is made into a ceramic sintered body, it can be applied to products such as hip joint prostheses, sliding bearings, and ceramic splitters.

[0126] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A ZTA ceramic material, characterized in that: It comprises a ceramic matrix and an additive; the additive comprises spinel; the molecular formula of the spinel is AB2O4, wherein A is selected from at least two of Zn, Mg and Ca, and B is Al.

2. The ZTA ceramic material according to claim 1, characterized in that: The mass ratio of the ceramic matrix to the spinel is (18.4-199):

1.

3. The ZTA ceramic material according to claim 1, characterized in that: The additive also includes at least one of strontium aluminate and chromium oxide; Alternatively, the additive further comprises strontium aluminate and chromium oxide; taking the total mass percentage of the ZTA ceramic material as 100%, the mass percentage of the strontium aluminate is 0.5-3%; and the mass percentage of the chromium oxide is 0.1-0.5%.

4. The ZTA ceramic material according to claim 1 or 2, characterized in that: The spinel is (Zn 1-x-y Mg x Ca y )Al2O4, wherein 0≤x<0.3, 0≤y<0.3, and x and y are not 0 at the same time.

5. The ZTA ceramic material according to claim 4, characterized in that: The spinel is (Zn 1-x-y Mg x Ca y )Al2O4, wherein 0.05≤x<0.3, 0.05≤y<0.

3.

6. The ZTA ceramic material according to claim 1, characterized in that: The spinel is prepared by mixing at least two selected from magnesium alkoxide, zinc alkoxide and calcium salt with aluminum alkoxide, followed by hydrolysis reaction, aging and calcining.

7. The ZTA ceramic material according to claim 6, characterized in that: The aging time is 1 to 3 hours; And / or, the temperature of the hydrolysis reaction is 55-75°C; And / or, the calcination temperature is 650°C to 950°C; And / or, the calcination time is 2h to 10h.

8. The method for preparing the ZTA ceramic material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: mixing various raw materials for preparing ZTA ceramic materials, pressing and forming, and obtaining a green body; S2: Debinding the green body and then calcining it, and then hot isostatic pressing it and then annealing it to obtain the ZTA ceramic material.

9. A ceramic product, characterized in that: The ceramic product is made of raw materials including the ZTA ceramic material described in any one of claims 1 to 7; the ceramic product is selected from joint prosthesis, sliding bearing or ceramic splitter.

10. Use of the ZTA ceramic material according to any one of claims 1 to 7 in the preparation of medical materials or electronic products.

Citation Information

Patent Citations

  • Sintered moulded body

    CN101702903A

  • Ceramic material

    CN101730672A

  • High-strength SrO-Cr2O3-ZTA ceramic and preparation method thereof

    CN115872728A

  • Preparation and application of artificial hip joint prosthesis ceramic

    CN117486587A

  • Ceramics with high toughness, strength and hardness

    US5002911A